Influence Tourist Sustainable to Preservation Environment and Culture: Review Global Literature - Abozi, Ezinne (Journal of Global Tourism, 2024)
Tourist sustainable become Topic central in efforts guard sustainability environment and culture, especially in destinations tourism that experiences pressure from the height amount visits. The background of this research is increasing global awareness of importance friendly tourism environment and oriented culture as solution to maintain sustainability environment at a time honor wisdom local. The purpose of this study is to understand influence implementation tourist sustainable to preservation environment and culture through review global literature, which includes studies from various countries with different challenges and successes. The method used is approach review literature systematic, collecting and analyzing literature scientific from various source related implementation tourist sustainable in various regions. The results of this study indicate that tourist sustainable own influence significant positive to preservation environment and culture, especially through subtraction impact negative environment and improvement participation public local in management tourism. However, there are also challenges in its implementation, such as need will supportive policies as well as supervision sustainable. This article is expected to provide insight comprehensive for stakeholder’s interest in understanding importance tourist sustainable as tool preservation environment and culture.